The Cryptocurrency Market And Financial Stability In The Context of Multiple Crises - Anamaria - Geanina MACOVEI; Mihaela TULVINSCHI; Marian SOCOLIUC; Anatol MELEGA (Communications of International Proceedings, 2022)
Cryptocurrencies are an atypical economic reality that share some characteristics and functionalities with elements such as money, commodities, stocks and assets, but do not cover all the requirements to be included in any of these categories. Cryptocurrencies are at the junction of innovation and financial development. This study is structured into three main objectives: O1 - to conduct an analysis on the literature concerning the emergence in the economic context of cryptocurrency and blockchain technology, by reference to the used scientific terminology and the assigned definitions to the concepts operating in the field;  O2 – to conduct a meta-analysis of trends in research and approach to cryptocurrencies and O3 - to determine the trend of the Bitcoin cryptocurrency over the period of 2012-2022, which could be used in forecasting the evolution of its price in the post-pandemic period and under the influence of the energy crisis caused by the armed conflict in Ukraine.
Keywords: cryptocurrencies; bitcoin; digital assets; time series.